2020
DOI: 10.3390/cancers12030639
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Adrenal Insufficiency Is Frequent After Adjuvant Mitotane Therapy in Patients with Adrenocortical Carcinoma

Abstract: Mitotane is a steroidogenesis inhibitor and adrenolytic drug used for treatment of adrenocortical cancer (ACC). Mitotane therapy causes adrenal insufficiency requiring glucocorticoid replacement in all patients. However, it is unclear whether chronic therapy with mitotane induces complete destruction of zona fasciculata and whether hypothalamic-pituitary-adrenal (HPA) axis can recover after treatment cessation. Our objective was to assess the HPA axis recovery in a cohort of patients after cessation of adjuvan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Only three studies specified the need for increased steroid coverage due to serum ACTH level elevation, or to signs and symptoms of adrenal insufficiency, as an endocrine adverse event (13/53 patients, 24.5%) [ 19 , 22 , 40 ]. Mineralocorticoid replacement was administered in a total of 67 of 182 patients in six studies [ 21 , 29 , 31 , 34 , 40 , 43 ]. Moreover, another study reported the need for fludrocortisone replacement therapy, but the proportion of patients was unclear [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only three studies specified the need for increased steroid coverage due to serum ACTH level elevation, or to signs and symptoms of adrenal insufficiency, as an endocrine adverse event (13/53 patients, 24.5%) [ 19 , 22 , 40 ]. Mineralocorticoid replacement was administered in a total of 67 of 182 patients in six studies [ 21 , 29 , 31 , 34 , 40 , 43 ]. Moreover, another study reported the need for fludrocortisone replacement therapy, but the proportion of patients was unclear [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen of 24 patients tested with ACTH stimulation test regained adrenal function after discontinuation of mitotane. This confirms a recent study by Poirier at al., who found 78% of patients treated with adjuvant mitotane to completely recover their adrenal function and thus discontinue glucocorticoid replacement 24 . Hypotheses explaining prolonged adrenal insufficiency, are a long‐lasting inhibitory effect on secretion of ACTH from the pituitary 25 or that interparenchymal and intraglandular levels of mitotane remain at a sufficient level to inhibit the steroidogenesis long after plasma mitotane concentration become undetectable 7 …”
Section: Discussionmentioning
confidence: 99%
“…In CD men, gynecomastia is also reported (17.6–50%), as mitotane also acts on gonadal steroidogenesis, impairing testicular androgen production ( 4 , 60 ). Moreover, the adrenolytic action of mitotane usually leads to AI, requiring therefore glucocorticoid replacement, although the AI may be reversible after mitotane withdrawal ( 4 , 60 ); particularly, a recent study on ACC patients exposed to mitotane in long-term treatments (at least 24 months) has shown that hypothalamus-pituitary-adrenal axis recovery may be present in around 78% of patients, with a mean time to recovery of 2.7 years ( 104 ). Despite the relevant number of CD patients treated with mitotane, all the available studies on mitotane as a treatment for CD are single-center, non-controlled studies, and two of the oldest studies included also patients undergone pituitary irradiation, potentially biasing the overall results ( 105 , 106 ).…”
Section: Adrenal-directed Drugsmentioning
confidence: 99%